2009
DOI: 10.2166/wqrj.2009.020
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Removal of Copper and Lead from Industrial Wastewater: Mass Transport Enhancement

Abstract: The effects of ultrasonic frequencies on both the mass transport process and diffusion layer were investigated during electrochemical treatment. The rates of mass transfer at a stainless steel cathode were measured for copper and lead in dilute acidified copper sulphate and lead nitrate solutions at different ultrasonic frequencies. Concentrations in bulk solution were determined by atomic absorption spectrophotometer. By increasing frequencies from 40 to 100 kHz, a high value for the mass transfer coefficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Unfortunately, the specific values of the ultrasonic power or the cathodic material have not always been reported for all experiments. The results of various studies [52][53][54] dealing with copper removal conclude that an improvement in the deposition rate is observed with an ultrasonically agitated bath. Farooq et al [53] used electrodeposition and ultrasound at 35 kHz to remove copper in wastewater.…”
Section: Power Ultrasound In Electrochemistrymentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, the specific values of the ultrasonic power or the cathodic material have not always been reported for all experiments. The results of various studies [52][53][54] dealing with copper removal conclude that an improvement in the deposition rate is observed with an ultrasonically agitated bath. Farooq et al [53] used electrodeposition and ultrasound at 35 kHz to remove copper in wastewater.…”
Section: Power Ultrasound In Electrochemistrymentioning
confidence: 99%
“…It is in diluted solutions that concentration polarization is high and the application of ultrasound is particularly beneficial. The effects of ultrasonic [54] frequency on both the mass transport process and the diffusion layer were also investigated during electrochemical deposition. By increasing frequencies from 40 to 100 kHz, a high value for the mass transport coefficient was observed.…”
Section: Power Ultrasound In Electrochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers with various cell designs have attempted removal of copper from solutions with varying degrees of achievements and improvements [5][6][7][8][9][10][11][12][13][14][15][16][17][18]. All of these researches were done keeping either the applied potential or the applied current constant during an experimental run and none of them used sodium chloride as supporting electrolyte.…”
Section: Introductionmentioning
confidence: 99%
“…Basha et al [1] studied the electrodeposition of copper at different initial pH values but they did not follow how the pH changed during electrolysis. Yaqub et al [11] investigated the electrolytic removal of Cu and Pb at different pH conditions and reported that the optimum pH range was 3-3.5 in the presence of ultrasound enhancement.…”
Section: Introductionmentioning
confidence: 99%